N-type doped amorphous Si thin film on a surface of rough current collector as anode for Li-ion batteries [Article] - Mukanova, Aliya; Nurpeissova, Arailym; Zharbossyn, Assem; Kim, Sung-Soo; Myronov, Maksym; Bakenov, Zhumabay (My University, 2018)
Abstract In this study, we report on the preparation of n-type doped ∼ 400 nm thick amorphous Si thin film on a surface of 9µm rough current collector. The electrochemical cycling test of designed anodes revealed that Si thin film on the surface of rougn exhibited stable capacity retention (∼67µAhcm-2) for 120 cycles. Rate capability test showed the unaltered performance of prepared electrode after applying a current rates up to 300µAcm-2
https://www.sciencedirect.com/science/article/pii/S2214785318318868
Keywords: rough current collector; silicon; thin film; n-type doped; amorphous; magnetron sputtering; lithium ion battery